KOMPETENSI KEPALA SEKOLAH DALAM INSTRUCTIONAL LEADERSHIP SD NEGERI BERPOTENSI BENCANA DI KABUPATEN MAGELANG - Rasidi, Rasidi; Istiningsih, Galih; Purwandari, Septiyati (Universitas Muhammadiyah Jakarta, 2017)
In particular, this study aimed at investiating to what extent the conditions and dominat cators, affecting in the headmaster’ instructional leadership competencies, for each potential disaster state elementary school in district of Magelang, the researchers used mixed methods studies that involve integrating quantitative (the preliminary data) and qualitaive (the further date)descriptive date analysis. The respondents of this study were the headmasters’ with their role as instructional leader of their state elementary schools. Based om the finding of qualitative descriptive analysis, the condition of the headmasters’ instructional leadeship competencies at potencial disaster state elemetary school of Krinjing 2 Magelang, was in good category. A totalscore headmasters’ instructional leaderships competencies obtained inm this study is 922. The total score was then compareted to the maximum score to know how many percent the headmasters’competencies analyzed. The result showed the total competency is 82,59%. The dominant factors affecting in the headmasters’ instructional leadership competencies are: 1) the headmaster as an instructional leader should has clear and understandable the organizational vision, 2) there is an effort getting near to the students, 3)involving teacher in decision making and so forth, 4)creating a steady/fixed curiculum, and it should be dynamic, 5)making a strong and profitable school cooperation network